2019
DOI: 10.2478/nor-2019-0034
|View full text |Cite
|
Sign up to set email alerts
|

Journalism and the political structure

Abstract: This article assumes a media system perspective on the local news media structure in Norway, using a dataset of 847,487 news articles collected from 156 Norwegian news outlets in 2015–2017. Using a series of hypotheses, the analysis uses Latent Dirichlet Allocation (LDA) topic modelling to ascertain to what extent local journalism meets community information needs through infrastructure, output and performance. The analysis finds that the size of the publisher and the size of the community covered matter more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 50 publications
0
1
0
1
Order By: Relevance
“…Mathisen (2010) showed that in local media in Norway, journalists and sources are mutually dependent, as they need to interact over and over both in the roles of sources and journalists but also in other capacities in the local society. Sjøvaag et al, (2019) showed that the size and isolation of local media systems impact on journalism's local community and accountability function in Norway.…”
Section: Size As the Number Of Overlapping Role-relationshipsmentioning
confidence: 99%
“…Mathisen (2010) showed that in local media in Norway, journalists and sources are mutually dependent, as they need to interact over and over both in the roles of sources and journalists but also in other capacities in the local society. Sjøvaag et al, (2019) showed that the size and isolation of local media systems impact on journalism's local community and accountability function in Norway.…”
Section: Size As the Number Of Overlapping Role-relationshipsmentioning
confidence: 99%
“…Denne analysen er metodisk ulik tidligere undersøkelser og er et forsøk på å finne ut hvordan vi gjør studier av politisk journalistikk der vi har tilgang til tilnaermet ubegrensede mengder mediedata (se også Sjøvaag, Pedersen & Laegreid, 2019). Utfordringene ligger ikke lenger i å samle data, men å gjøre analysene teoribaserte og meningsfulle.…”
Section: Innledningunclassified